Pengembangan Model Keselamatan pada Transportasi Kereta Api (Studi Kasus: PT. Kereta Komuter Indonesia) - Nilla Nilla; Parwadi Moengin (JIEMS (Journal of Industrial Engineering and Management Systems), 2019)
The application of safety is an important matter in carrying out activities inland transportation including railroad transportation. Jabodetabek travel routes are handled directly by PT. Kereta Komuter Indonesia. This activity certainly requires a lot of human labor so safety is very important in this regard. With the existence of safety arrangements, it will avoid any related things from accidents or losses due to the delay in the completion of work caused by the inaccurate company safety management system. Therefore each element involved in each activity requires further knowledge and understanding of the core factors that are in accordance with the safety management system used. Referring to this approach, research is carried out on the railroad industry in Indonesia by developing a safety model in the railway industry. The research was conducted by finding the right literature and then developing a model for the factors considered appropriate to be applied to the safety management system in railroad transportation in Indonesia. After the model was developed, the model was confirmed by the Confirmatory Factor Analysis (CFA) approach with the Structural Equation Modeling (SEM) method. The results of the study will prove that the factors developed in the safety model are positively related to the implementation of commuter train safety management in Indonesia.